Challenges in Education Posed by the Fourth Industrial Revolution - Ruch, Hubert; Florentine, Natthakitta; Pholpuntin, Sirote; Chaleysub, Sukhum; Tungdamnernsawad, Supaporn; Udomtamanupab, Siratam (ASEAN Journal of Education, 2024)
This review article provides an overview of the challenges that the Fourth Industrial Revolution (4IR) may pose for education as reflected in scientific articles, white papers and other up-to-date publications. The approach taken here does not make distinctions among different educational levels but instead aims to highlight overarching challenges across the education sector as a whole, providing the opportunity to identify general or cross-cutting risks that may arise from the 4IR. The topic of digitization - one of the main pillars of the 4IR - seems highly controversial within the research studies examined, with disagreement regarding both possible harmful effects of digitizing classrooms and the fundamental benefits of multimedia. There seems to be a clear trend of many authors to recommend necessary adjustments that enable various stakeholders to adapt to the developments prompted by the 4IR. The main recommendations here are flexibility, personal responsibility, and self-reliance. Relatively few researchers - such as Yong Zhao - recommend active engagement in order to consciously influence or even delay the dynamics of the 4IR. Leaders in particular are called upon to make greater efforts to adapt, e.g. by implementing AI and AI-powered personalized learning into pedagogies and curricula, teacher support in using AI tools and developing ethical standards, fostering access and equity, data-driven decision making, future-ready skills development, partnerships with tech companies, continual adaptation and lifelong learning, and taking into account human aspects regarding the digitalization of education, such as the impact on people when theThis review article provides an overview of the challenges that the Fourth Industrial Revolution (4IR) may pose for education as reflected in scientific articles, white papers and other up-to-date publications. The approach taken here does not make distinctions among different educational levels but instead aims to highlight overarching challenges across the education sector as a whole, providing the opportunity to identify general or cross-cutting risks that may arise from the 4IR. The topic of digitization-one of the main pillars of the 4IR-seems highly controversial within the research studies examined, with disagreement regarding both possible harmful effects of digitizing classrooms and the fundamental benefits of multimedia. There seems to be a clear trend of many authors to recommend necessary adjustments that enable various stakeholders to adapt to the developments prompted by the 4IR. The main recommendations here are flexibility, personal responsibility, and self-reliance. Relatively few researchers-such as Yong Zhao-recommend active engagement in order to consciously influence or even delay the dynamics of the 4IR. Leaders in particular are called upon to make greater efforts to adapt, e.g. by implementing AI and AI-powered personalized learning into pedagogies and curricula, teacher support in using AI tools and developing ethical standards, fostering access and equity, data- driven decision making, future-ready skills development, partnerships with tech companies, continual adaptation and lifelong learning, and taking into account human aspects regarding the digitalization of education, such as the impact on people when they learn and work on computer screens or in virtual worlds.y learn and work on computer screens or in virtual worlds.